Yield Spread Estimation with Credit Events (Journal of Informatics and Mathematical Sciences, 2016)
We study a problem of modeling impacts of credit rating migration on spread curves. We consider the construction of credit curves adopting specific groups of representative issuers for credit rating by taking their average spread. Then, we introduce the method of grouping in full grade to handle the case for which a statistically representative set of issuers does not exist. Finally, empirical experiment shows the efficiency of our approach.
Keywords: Migration risk; Default risk; Spreads; Spread shock; Multiplicative shock; Additive shock; Credit rating migration